The Employer Perspective on Paid Leave & the FMLA - Peter A. Susser (Washington University Journal of Law & Policy, 2004)
This Essay explores: (1) the initial treatment of compensated leave under the FMLA and its implementing regulations; (2) the Clinton Administration’s regulatory experimentation with paid leave protections for certain forms of FMLA-protected leave; and (3) related developments at the state level—particularly California’s 2002 paid leave legislation—to examine the nature and direction of this debate.
Keywords: Parental leave; Family and Medical Leave Act of 1993